The Use of Structurally Augmented 3D Printed Cages in Segmental Defects of the Tibial Shaft. Issue 4 (16th October 2019) - Tracey, Joseph; Parekh, Selene
Category: Trauma, Emerging Technology Introduction/Purpose: Modern day management of segmental defects of the tibia shaft (SDTS) involve autologous nonvascularized grafts, autologous vascularized contralateral fibula grafts, as well as bone transport distraction osteogenesis, however single stage titanium cages with adjuvant biologics continue to demonstrate advantages. With the development of advanced additive manufacturing further modalities such as complex variable lattice structure and submicron texture may be incorporated into custom fit implants. We aim to further investigate the potential of this technology on osteoinduction, and hypothesize early bone in-growth. Methods: A retrospective analysis was performed on 3 patients undergoing custom cage implantation for SDTS. All three patients were male with an average age of 60, 2 patients were diabetic, and one was a smoker. All three cases were performed in the setting of post-infection salvage. Pertinent demographic and clinical history was retrieved through the medical record. Results: All three cases were uncomplicated in the post-surgical period, and early bone in-growth was demonstrated in successive follow-ups. One case was single-staged and built into a prior total ankle arthroplasty, the next was a deformity correcting intramedullary rod that became infected requiring two-stage salvage with an antibiotic spacer and subsequent custom cage with Intramedullary rod supplementation, and the third case was a two-stage trauma salvage initially using an antibiotic spacer with subsequent custom cage implantation. Conclusion: 3D printed custom cages were found to be a safe and efficacious option for management of SDTS, with demonstrated early bone in-growth. Considering the incorporation of advanced additive manufacturing techniques, strong implementations may be present for salvage cases.